Public Complaints on Municipal services: A Perspectives from Internal and External Customers - Zakaria, Zaherawati; Ngah, Kamarudin; Noordin, Nazni; Aminuddin, Adnan (2017)
The previous studies mainly address the lack of efforts and initiatives of the authorities in organizing effective participation programs in waste management, cleanliness, drainage and culverts affairs. The Public Complaints Bureau stepped up efforts to promptly deal with complaints received from the public. On average, 50 per cent of complaints received were on the failure or delays in attending or responding to the needs of customers effectively. By using the quantitative and qualitative methods approach, this study attempts to examine the satisfaction of public complaints process that influences the community in Sungai Petani. The extent of satisfaction level in municipal services, both &om internal customers and external customers attempt to establish association between customer satisfaction and social characteristics such as feedback towards complaint and information channel as resident and customer. Based on the findings, in order to make customer satisfiaction on municipal services, future strategies need to be done in order to more satisfactory by the focus groups.